Leon Sachs. The Pedagogical Imagination: The Republican Legacy in Twenty-First Century French Literature and Film. Lincoln/London: U of Nebraska P, 2014. xi + 227 pp. - Zachary R. Hagins (Studies in 20th & 21st Century Literature, 2015)
Review of Leon Sachs. The Pedagogical Imagination: The Republican Legacy in Twenty-First Century French Literature and Film. Lincoln/London: U of Nebraska P, 2014. xi + 227 pp.
Keywords: republican; pedagogy; education; formalism; France